Advances in biological and medical physics. - Lawrence, John H. (John Hundale), 1904-1991; Gofman, John W.; Hayes, Thomas L. (Thomas Leo), 1927- (Academic Press, 1980)
Advances in Biological and Medical Physics, Volume 17 covers articles on the advances in biological and medical physics. The book presents articles on energy transfer dynamics; the molecular mechanism of DNA repair after ionizing radiation; and mechanisms of prereplication repair of DNA breaks in gamma-irradiated E. coli cells. The text then describes articles about damages to DNA that result in neoplastic transformation; the nature of radiation and chemically-induced lesions and the role of cellular mechanisms in cell survival and mutagenesis; as well as the nature of the target in the biolo.